Personalisation of internet based business office layout - Chua, S.J.L.; O. Shahruddin; A.S. Ali; C.P., Au-Yong; N.F. Azmi (Penerbit Universiti Kebangsaan Malaysia, 2017)
In current era, the nature of business is ever-changing where communication and interaction between office workers are encouraged as the scope of work for office is expanding. Traditional offices with identical cubicles separated with panels are ineffective because not all workers are in the same activity mode at the same time. Providing and maintaining a comfortable and healthy office environment is vital consideration in designing an office. The interior layout design parameter involved are the comfortability of furniture, surrounding temperature, amount of lighting provided, the quality of indoor air, spatial arrangement, the condition of environment in terms of noise and privacy, and finally the 2D horizontal and vertical layout. This research seeks to identify the factors of interior layout design parameter that will affect the productivity and performance of the workers. The research is conducted using quantitative method. Questionnaire is distributed to the building occupants to evaluate and obtain their opinion on the satisfaction level of the layout at their workplace. The user satisfaction and perception on the existing interior layout design are gathered by using a questionnaire survey. The study proves that the workers are most satisfied with the lighting and least satisfied with the furniture at their existing interior layout design. The workers from both case studies agreed that the interior layout design parameter that has the most effect on the productivity is the environment noise and privacy; while 2D horizontal and vertical layout has the least effect.